Analysis of Financial Statement and Sustainability of CDMA Service Provider Company (A Case of PT Smartfren Tbk and PT Bakrie Telecom Tbk) - Ayu, Athira Azalika; Darmansyah, Asep (Journal of Business and Management, 2015)
Abstract. Telecommunications is very vital to help people socialize and live. Various means are provided to facilitate the course of the telecommunications activities. One of them is the establishment of telecommunication service provider company. In Indonesia itself, there are to types of telecommunication service provider, which are GSM and CDMA. In the past year, CDMA service provider companies suffer bankruptcy one by one leaves only two companies remaining named PT Telecommunication X and PT Telecommunication Y. The purpose of this research is to determine the financial performance of the companies during the period 2011 through 2014 at the CDMA service provider companies and to determine the sustainability prediction in the future at the CDMA service provider companies. If those companies are aware of its financial condition and able to improve its performance, the company would likely to survive in telecommunication industry. The financial performance of both companies were analyzed and compared using financial ratio calculation and trend financial statement. For the sustainability analysis, Altman Z-Score is the method used in this research to predict a future bankruptcy indicator. The result of analysis shows that PT Telecommunication X and PT Telecommunication Y are not performing a good financial performance and are in the state of bankruptcy based on Altman Z-Score analysis.Â Keywords: Telecommunication industry; financial ratios; Altman Z-Score; sustainability analysis; trend analysis, financial performance.